Comparison of bupivacaine alone and in combination with fentanyl or pethidine for bilateral infraorbital nerve block for postoperative analgesia in paediatric patients for cleft lip repair: A prospective randomized double blind study - Rajesh S Mane; C S Sanikop; Vithal K Dhulkhed; Tuhina Gupta (Wolters Kluwer Medknow Publications, 2011)
Background: Cleft lip repair is one of the common surgeries performed in India and the usual method used for post operative analgesia is perioperative opioids and NSAIDs. There has been an increase in use of regional techniques and Opioids are the common adjuvants but their efficacy and safety have not been studied extensively in children. Patients & Methods: A prospective, randomized, double blind study was done to compare the efficacy, duration and safety of intraoral infraorbital nerve block on post operative pain relief using bupivacaine alone or in combination with fentanylor pethidine in paediatric cleft lip repair. 45 children between the age group 5 - 60 months undergoing cleft lip surgery randomly allocated into 3 groups of 15 each received bilateral intraoral infraorbital nerve block with 0.75ml of solution. Group B received 0.25% bupivacaine; group P received 0.25% bupivacaine with 0.25mg kg -1 pethidine, group F received 0.25% bupivacaine with 0.25microgm kg -1 fentanyl. Sedation after recovery, post operative pain intensity and duration of post operative analgesia were assessed using Modified Hannallah Pain Score. Results : The mean duration of analgesia was 17.8 hrs in Group B, 23.53 hrs in Group F and 35.13 hrs in Group P. There was statistically significant difference between the means of the three groups- ANOVA (p < 0.05). Conclusion: Thus we conclude that addition of fentanyl or pethidine to bupivacaine for Bilateral Intraoral Infraorbital Nerve Block prolong the duration of analgesia with no complications and can be used safely in paediatric patients.